Gambaran Perilaku Keluarga dalam Menyimpan dan Membuang Obat Antibiotik di Kecamatan Pariangan, Kabupaten Tanah Datar - Zulkarni, Zulkarni; Syofyan, Syofyan; Triyanda, Zola (JSFK (Jurnal Sains Farmasi & Klinis), 2020)
Risk factors for drug-related incidents can begins from problems in getting, using, storing and disposing of inappropriate drugs including antibiotics. The problem of antibiotic drugs has become a global problem that needs serious attention, including in Indonesia. The purpose of this study was to describe the behavior of families in storing and disposing of antibiotic drugs in Pariangan Subdistrict, Tanah Datar, Indonesia. The study used a cross sectional design with a purposive sampling technique. Based on the calculation of the number of samples by using Slovin formula, there were 100 families in Pariangan Subdistrict, Tanah Datar District that met the inclusion and exclusion criteria. This study used an instrument in the form of a questionnaire that met the validity and reliability test requirements. The data were analyzed by SPSS. The results showed that the family’s behavior in storing and disposing of antibiotics was sufficient with mean values of 6.07 and 6.90, respectively. Based on the correlation test, it can be concluded that there is no relationship between knowledge of families regarding of pharmacist profession and antibiotic drugs with family behavior in storing and disposing of antibiotics as indicated by a value of r = 0.163.